Using the water-energy-food nexus to enhance Egypt’s cooperation with Nile Basin countries - Kheireldin, Aly Taher (AUC Knowledge Fountain, 2016)
In the coming decades, the World will be facing severe challenges in terms of water, energy and food through increased water use, increased energy demand and increased food demand and shifting diets. Those challenges are foreseen to be amplified due to climate change effects. Egypt is a country struggling to achieve water, energy and food security, which are key issues in achieving national security. Egypt is facing another major challenge regarding its main water resource Nile River. Ethiopia is currently undergoing the construction of a huge dam on the Blue Nile which is the Grand Ethiopian Renaissance Dam (GERD). The purpose of the research is to attempt to mitigate the effect of the GERD on Egypt through cooperation with the Nile Basin countries on their Water-Energy-Food Nexus (WEF Nexus). The grand Ethiopian Renaissance dam (GERD) is a mega hydro-electric project currently under construction on the Blue Nile. It is planned to have a 74 BCM capacity reservoir and a power generation capacity of 6,000 MW. If not agreed appropriately, the filling of the GERD reservoir might have significant impacts on the Aswan High Dam. A policy framework was developed for the water-energy-food nexus for Egypt and the Nile Basin. In Egypt, it is suggested to create a Supreme Council for Water, Energy and Food which includes all the relevant ministries. For the Nile Basin, a Nile Basin WEF is suggested, whose decisions should be legally binding for Nile Basin countries. Examples were provided on the project/programme level that could have benefited from the WEF synergy, like the reclamation of 1.5 million feddans and the expansion of the electricity generation sector. An institutional arrangement was developed, which is applicable for Egypt and the Nile Basin countries. The arrangement is done through a methodology which encourages the prioritization of projects that take into consideration the WEF nexus. On the Nile Basin level, examples were given for potential projects that could benefit from the WEF synergy if the basin is thought of as one unit. Examples provided included the expansion of green water utilization and integration of electricity grids. The policy framework showed that the GERD itself can be viewed as an opportunity for cooperation if the right policy framework is developed among the basin countries.